(untitled) ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2024)
Background: The choice of the hotel is shaped by Customer relationship management strategies commonly termed as CRM. CRM is therefore essential to positively influence purchase decisions of hotel guests, retaining travelers and satisfying the customers, or else risks driving them away. Objectives: The first objective of the study was to identify the key CRM strategies exercised by hotels to influence customer’s hotel selection. The second objective of the study was to analyze the key influence of important hotels CRM strategies on customer’s hotel selection. Methodology: The study focuses on star-category hotels in Bhopal, with data collected from travelers over 18 years using convenience sampling. A structured questionnaire, distributed via Google Forms, gathered primary data on demographic profiles and key CRM strategies, with responses rated on a five-point Likert scale. Secondary data came from reports, research papers, and articles. Data was collected in July and August 2024. The first objective, identifying key CRM strategies, was addressed through previous studies, while the second objective, analyzing CRM’s influence on hotel selection, was achieved using weighted mean scores. Results: After extensive study of previous literature, key CRM strategies found were personalized guest experiences, loyalty programs, staff training and empowerment, events and activities, special offers and promotions, efficient booking processes, pre-arrival communication, in-room technology, dynamic pricing, social media engagement and post-stay follow-up. The second objective results indicated that staff training and empowerment had the highest influence on customer hotel selection, with a weighted mean score of 3.25, followed by special offers and promotions (3.23), and dynamic pricing (3.22). Conclusions: These factors will afford a prescription for enhancing customer acquisition and retention in the context of the hotel organization.